Withstanding the test of time: Multisensory cues improve the delayed retention of incidental learning. Issue 1 (5th September 2018) - Broadbent, Hannah J.; Osborne, Tamsin; Mareschal, Denis; Kirkham, Natasha Z.
Abstract: Multisensory tools are commonly employed within educational settings (e.g. Carter & Stephenson, 2012 ), and there is a growing body of literature advocating the benefits of presenting children with multisensory information over unisensory cues for learning (Baker & Jordan, 2015 ; Jordan & Baker, 2011 ). This is even the case when the informative cues are only arbitrarily related (Broadbent, White, Mareschal, & Kirkham, 2017 ). However, the delayed retention of learning following exposure to multisensory compared to unisensory cues has not been evaluated, and has important implications for the utility of multisensory educational tools. This study examined the retention of incidental categorical learning in 5‐, 7‐ and 9‐year‐olds ( N = 181) using either unisensory or multisensory cues. Results found significantly greater retention of learning following multisensory cue exposure than with unisensory information when category knowledge was tested following a 24‐hour period of delay. No age‐related changes were found, suggesting that multisensory information can facilitate the retention of learning across this age range. Abstract : Retention of multisensory learning over 24 hours in 5‐9 year‐olds was examined. Using a novel category learning task, results showed significantly greater retention of incidental knowledge of category boundaries as well as greater depth of categorical information following multisensory compared to unisensory cues.